Correlation of the running-based anaerobic sprint test (RAST) and performance on the 100m, 200m and 400m distance tests - Paradisis, G. P.; Tziortzis, S.; Zacharogiannis, E.; Smirniotou, A.; Karatzanos, L. (Journal of Human Movement Studies, 2005)
The aim of this study was to investigate the correlation between the running-based anaerobic sprint test (RAST) and the performance on the 100m, 200m and 400m running tests. Twenty eight subjects performed a 35m distance 6 times maximally with a 10s rest between the repetitions. Based on the RAST, the maximum, minimum and average power, as well as two fatigue indexes were calculated and correlated with the performance in the 100m, 200m and 400m distances. The correlation coefficients were statistically significant with an exception of the fatigue index 2, where the performance of the 100m was highly correlated and the 200m and 400m were highly correlated with the average power. It could be concluded that RAST correlated significantly with the performance in short distances and it could predict any changes in the performance and could be used as a training tool in anaerobic training.